Enhanced biological performance of Sr2+-doped nanorods on titanium implants by surface thermal-chemical treatment - Xinrui Dai; Jianghui Zhao; Shengcai Qi; Ping Liu; Wei Li; Ke Zhang; Xiaohong Chen; Fengcang Ma (Journal of Materials Science: Materials in Medicine)
Abstract Titanium alloys, as artificial implants for orthopedic diseases, are prone to aseptic loosening and infection after surgery because their smooth surface restricts the attachment and movement of osteoblasts, resulting in a lack of osteogenic and antimicrobial properties. This study aimed to prepare SrTiO3 nanostructures with varying Sr content on the surface of titanium through a thermal-chemical treatment, enhancing the osteogenic capacity of titanium while providing antibacterial properties. The results indicated that the SrTiO3 nanostructures are primarily composed of pure titanium and SrTiO3 phases, exhibiting a rod-like surface morphology. Sr is uniformly distributed across the surface of the samples, and increasing the Sr content does not alter the morphology of the nanostructures. Wettability tests demonstrated that the SrTiO3 nanostructures exhibited superhydrophilicity, promoting cell adhesion. Electrochemical tests revealed that the SrTiO3 nanostructures prepared on the titanium surface significantly enhanced its corrosion resistance. After 14 days of immersion in simulated body fluids, a significant amount of hydroxyapatite formed on the surface of STN3, indicating that the SrTiO3 nanostructures possess good bioactivity. In vitro antimicrobial tests demonstrated that SrTiO3 nanostructures were effective against both Escherichia coli and Staphylococcus aureus, with the antimicrobial rates increasing alongside the Sr content, reaching 48.1% and 38.6%, respectively. Graphical Abstract